In memory of the first professor of the Department of Pathology, Therapy and Clinics of the Imperial Kazan University Johann Friedrich Erdman - L. K. Bombina; D. I. Abdulganieva; A. A. Galiullina; A. R. Salimzyanova; T. N. Khalfina (Кардиоваскулярная терапия и профилактика, 2022)
The article is dedicated to Professor Fedor Khristoforovich Erdman — a doctor, scientist, teacher, the first head of the Department of Pathology, Therapy and Clinics and the first dean of the Medical Faculty of the Imperial Kazan University. We considered his work within the Imperial Kazan University and Imperial Dorpat University, his contribution to the clinical teaching, the organization of a university clinic and a balneotherapy sanitarium. A number of papers written based on the results from the Kazan period of research are presented. The study summarizes the basic information about the professional and teaching role of Erdman F.Kh. in the history of Russian medicine.